2019
DOI: 10.1007/s40201-019-00366-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of doping zinc oxide nanoparticles with transition metals (Ag, Cu, Mn) on photocatalytic degradation of Direct Blue 15 dye under UV and visible light irradiation

Abstract: Background Azo dyes represent the most commonly used group of dyes in the textile industry. These organic dyes are mainly resistant to biodegradation and may exhibit toxic and carcinogenic properties. The purpose of this study was to investigate the effects of doping zinc oxide (ZnO) nanoparticles (NPs) with transition metals (silver, manganese, and copper) on the photocatalytic efficiency of ZnO NPs in the removal of Direct Blue 15 dye from aqueous environments under ultraviolet (UV) radiation and visible lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…A 1.5% Nd-Gd codoped ZnO resulted in 93% photocatalytic breakdown of MB in 180 min [67]. The photocatalytic efficiency of other doped zinc oxides for the degradation of various dyes can be seen in Table 1 [68][69][70][71][72][73][74][75][76][77]. Thus, it can be concluded that doping increases the photocatalytic characteristics of ZnO nanostructures.…”
Section: Use Of Zno For the Breakdown Of Dyesmentioning
confidence: 99%
“…A 1.5% Nd-Gd codoped ZnO resulted in 93% photocatalytic breakdown of MB in 180 min [67]. The photocatalytic efficiency of other doped zinc oxides for the degradation of various dyes can be seen in Table 1 [68][69][70][71][72][73][74][75][76][77]. Thus, it can be concluded that doping increases the photocatalytic characteristics of ZnO nanostructures.…”
Section: Use Of Zno For the Breakdown Of Dyesmentioning
confidence: 99%
“…It is well known the use of semiconductors like TiO 2 3 and ZnO for this purpose 4 . Likewise, it is known that the wide band gap of these metal oxides limits their use in the visible range 5 . Additionally, rapid recombination of hole-electrons pairs is another limitation of ZnO 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has become an important issue to extend the optical absorption of ZnO from the UV region to visible region for photocatalytic applications. Several methods have been proposed to improve properties of ZnO by controlling the size and morphology of particles [ 38 , 39 ], doping with metals and nonmetals [ 40 , 41 , 42 , 43 ] and coupling with other semiconductor catalysts [ 44 , 45 , 46 ]. The surface defects by introducing metal elements have been reported to play an important role in improving photocatalytic activities over a wide range of wavelengths by reducing the bandgap energy.…”
Section: Introductionmentioning
confidence: 99%